What We Know about Nasal Polyposis: The Clinician’s Point of View - Philippe Eloy; Gabriela Cornelia Musat (Sinusitis)
Nasal polyposis is defined as a Th2-driven chronic inflammation of the nose and sinus with polyps visible in the nasal fossae. It is a prevalent disease with a significant impact on health-related quality of life (HRQL). Allergies, allergic rhinitis, asthma, and aspirin intolerance are frequently associated. The management is individual. The first line of treatment is long-term treatment with intranasal corticosteroids. Oral corticosteroids should be used with caution. When the medical treatment fails, the patient is eligible for sinus surgery, which usually consists of a complete sphenoethmoidectomy. In the case of symptomatic recurrence after both medical and surgical treatment, biologics are currently a very promising treatment effective on all respiratory tracts. Dupilumab is considered in the literature to be the molecule of choice. However, besides the international guidelines published by EPOS and Euforea, the molecule prescribed depends also on its availability in each country and the criteria edited by the health authorities to receive reimbursement. Traditional medical treatment remains necessary as a complement to biologics. At the moment, there is no consensus on when the medical treatment can be stopped.